Tungsten Diselenide Patterning and Nanoribbon Formation by Gas‐Assisted Focused‐Helium‐Ion‐Beam‐Induced Etching. Issue 4 (24th February 2017) - Stanford, Michael G.; Pudasaini, Pushpa R.; Cross, Nicholas; Mahady, Kyle; Hoffman, Anna N.; Mandrus, David G.; Duscher, Gerd; Chisholm, Matthew F.; Rack, Philip D.
Abstract : A gas‐assisted focused‐helium‐ion beam‐induced etching (FIBIE) process is introduced, which accelerates direct‐write patterning of WSe2 relative to standard ion milling. The etching process utilizes the XeF2 precursor molecule to provide a chemical assist for enhanced material removal relative to ion sputtering. The FIBIE process enables high‐fidelity patterning of WSe2 with doses 5× lower than standard He + milling. This enables the formation of high‐resolution WSe2 nanoribbons with dimensions less than 10 nm. The WSe2 nanoribbons demonstrate high Raman anisotropy and nanoribbon electrical measurements are reported for the first time. The normalized on‐currents of field‐effect transistors reveal that the electron and hole currents are both suppressed and scale with the nanoribbon width, with the electron transport experiencing more degradation. However, on‐currents of nanoribbons created by the FIBIE process remain orders of magnitude greater than nanoribbons formed by standard He + milling. Scanning transmission electron microscopy and complementary Monte Carlo ion–solid simulations reveal that the reduced currents are partially due to ion‐induced damage in the WSe2 . Abstract : A gas‐assisted focused‐He + ‐induced etching strategy is used for direct‐write patterning of WSe2 . This enables the patterning of high‐fidelity and aligned nanoribbons with sub‐10 nm resolution. This process prevents the inclusion of prohibitive damage to the crystal lattice, which is common for He + ‐sputtering processes.